Poetry for children as an educational project by Alfonso Gatto - Mazzini, Alessandra (Rivista di Storia dell’Educazione, 2020)
In 1945 Alfonso Gatto published Il sigaro di fuoco. Poesie per bambini, a volume in which the author, who had already identified in art, urban planning and architecture the possible factors of a moral and civil progress of the nation, renews his ethical commitment. The collection becomes an opportunity to develop an idea and a practice of education, as well as a pedagogical model other than that proposed in the Fascist period. An unprecedented and courageous project that does not end with the end of the war. In the years of the economic boom, of the degeneration of consumption, the poet publishes for «children of all ages» Il vaporetto, feeling the urgency to make children’s literature the ultimate tool for building a model of life and civilization.